AB0491 High-resolution computed tomographic findings in patients with systemic sclerosis and their clinical correlations. (23rd January 2014) - Ponte, C. B.; Morais, F.; Campanilho-Marques, R.; Resende, C.; Pereira da Silva, J.
Abstract : Background: The thorax high-resolution computed tomography (HRCT) is the preferred radiological examination in the evaluation of interstitial lung disease (ILD) in SSc. Although directed primarily to the lung involvement in this disease, HRCT can give information about the oesophagus functional status, trough the presence of oesophageal dilatation 1 . Recent studies suggest that HRCT may also be helpful in screening for pulmonary hypertension (PH) through the assessment of the fibrosis extent and the diameter of the main pulmonary artery (MPAD). Objectives: To determine the prevalence of ILD and its different morphologic patterns in patients with SSc using HRCT. To correlate the presence of oesophageal dilatation, in the HRCT of these patients, with other clinical features communally associated to oesophageal dysfunction. To evaluate the imaging features on HRCT suggestive of PH and their comparison with echocardiograms with systolic pulmonary artery pressure (SPAP) measurements. Methods: We retrospectively retrieved the database of patients with systemic sclerosis seen in our Rheumatology outpatient clinic of Santa Maria Hospital, Lisbon, between January 2007 and December 2012. Only patients who had HRCT of the chest, pulmonary function tests (PFTs) and echocardiograms, within 6 months of each other, were included in the study. The HRCT chest was interpreted by a chest radiologist. The lung involvement was classified according to the presence of morphologic patterns characteristic of the different Idiopathic Interstitial Pneumonias (IIPs). Oesophageal dilatation was defined as a luminal coronal diameter of ≥9 mm in infra-aortic oesophagus. The maximum diameter of the main pulmonary artery (MPAD) was measured and considered to be increased when ≥29 mm. SPAP was measured echocardiogram, and a value ≥35 mm Hg was considered PH. Results: Forty five patients (42 women and 3 men), with a mean age of 55.4 ±15.5 years were included: 20 patients had limited SSc, 18 patients had diffuse SSc, 6 patients had Overlap Syndrome and 1 patient had SSc sine scleroderma. In 64.4% of patients was detected an IIP: 75.9% suggestive of NSIP, 13.8% suggestive of UIP and 10.3% unable to classify. There was no significant statistical difference between the presence of UIP or NSIP and the values of TLC (p 0.45) and DLCO (p 0.63) from the PFTs. Oesophageal dilatation was present in 68.9% of the patients, of which 90.3% had symptoms of dysphasia, esophageal motor dysfunction on manometry or oesophagitis in endoscopy. Also 28.5% of the patients without oesophageal dilatation in HRCT (31.1%) had these same clinical features. The MPAD was increased in 29.3% of the cases and only 41.7% of these patients had SPAP compatible with PH (all of them also with IIP). Conclusions: Considering the results presented here, we conclude that NSIP is the most common IIP in SSc. Other findings in the HRCT, such as oesophageal dilatation, showed a high specificity for this organ involvement and dysfunction in SSc. An increased MPAD, measured in the HRCT of these patients, didn't seem to be related with the presence of PH assessed by echocardiogram. References: Pandey AK et al. Oesophageal dilatation on high-resolution CT chest in systemic sclerosis:what does it signify? J Med Imaging Radiat Oncol. 2011 Dec;55:551-5 Disclosure of Interest: None Declared